2012
DOI: 10.1248/bpb.b12-00528
|View full text |Cite
|
Sign up to set email alerts
|

A Novel C–C Chemokine Receptor 2 Antagonist Prevents Progression of Albuminuria and Atherosclerosis in Mouse Models

Abstract: In conclusion, the results of this study indicate not only considerable therapeutic potential of CCR2 antagonists for diabetic nephropathy and atherosclerosis, but also that TLK-19705 would serve as a powerful tool in mechanistic investigation of these inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…To interrupt the CCL2-CCR2 axis, several types of inhibitors such as CCR2 antagonist, neutralizing antibody of CCL2, CCL2 mutant protein with property of inhibiting CCL2 singling and RNA interference technology have been investigated for treatment of cardiovascular disease, neurodegenerative disease, cancer, and chronic inflammatory diseases [24, 4044]. Our previous studies [1618] and the current study demonstrate the positive effects of 7ND, a dominant negative mutant CCL2, on mitigating wear particle-induced bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…To interrupt the CCL2-CCR2 axis, several types of inhibitors such as CCR2 antagonist, neutralizing antibody of CCL2, CCL2 mutant protein with property of inhibiting CCL2 singling and RNA interference technology have been investigated for treatment of cardiovascular disease, neurodegenerative disease, cancer, and chronic inflammatory diseases [24, 4044]. Our previous studies [1618] and the current study demonstrate the positive effects of 7ND, a dominant negative mutant CCL2, on mitigating wear particle-induced bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic nephropathy, there is increased CCL2 expression in the kidney and urine (3,28,29,42) and increased numbers of macrophages in the kidney (14,31). In diabetic leptin receptordeficient (db/db) mice, other CCR2 antagonists have slowed or blocked the increase in albuminuria that occurs over time in these mice, but a reduction in albuminuria relative to disease severity at start of the study has not been demonstrated (22,32,38,41). Here, we show that, in diabetic hCCR2 KI db/db mice, CCX140-B reduced albuminuria within 1 wk of treatment and maintained this benefit over the entire 6-wk treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular CCR2 expression is increased in patients with diabetic nephropathy (45). Diabetic mice deficient in CCL2 (9,10,45) or treated with CCR2 antagonists (20,22,32,38) exhibit reduced proteinuria.…”
mentioning
confidence: 99%
“…CCL2 is closely associated with the process of glomerular and interstitial inflammatory cell recruitment, such as macrophage cells. Hence, the blockade of the CCL-2/CCL-2 receptor (CCR-2) pathway could have considerable therapeutic potential for DN (161).…”
Section: Drugs Targeting Inflammationmentioning
confidence: 99%